Exploring Bank Value Through ESG and Ownership Structure with NPL as a Mediating Variable in a Climate-Conscious Context - Apriani Simatupang; Radityo Fajar Arianto; Arief Adi Wibowo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) and ownership structure on bank value, with Non-Performing Loans (NPLs) as a mediating variable, in the context of climate-conscious banking in Indonesia. A quantitative approach was used with panel data from 10 banks listed on the Indonesia Stock Exchange (IDX) during the period 2015–2024. The analysis was conducted using panel data regression and mediation tests. The results show that ownership structure has a significant positive effect on bank value, both directly and indirectly through a decrease in NPLs. This finding confirms that NPLs have a strong negative effect on bank value (measured by Price to Book Value/PBV) and act as a partial mediator. Conversely, ESG factors have no significant effect on NPLs or PBV, indicating that ESG implementation in Indonesian banks is still symbolic and has not yet had a tangible impact. The implications of this study are the importance of strengthening governance and risk management through ownership oversight, as well as the need for more concrete ESG implementation to improve the performance and long-term resilience of the banking sector.